2004
DOI: 10.1080/0960310042000211605
|View full text |Cite
|
Sign up to set email alerts
|

The performance of UK firms acquiring large cross-border and domestic takeover targets

Abstract: This paper focuses upon cross-border acquisitions. A three-way comparison is made between the post-takeover performance of UK acquirers of domestic UK, US, and Continental European targets between 1991 and 1996. This study examines if UK firms acquiring large takeover targets experience cumulative abnormal returns significantly different from zero up to two years after the acquisition. This study finds that UK firms acquiring large takeover targets experience negative cumulative abnormal returns over the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 28 publications
6
44
0
1
Order By: Relevance
“…Danbolt (1995) made a comparison study for acquiring firms from various countries and concluded that UK acquiring firms earn significant negative abnormal returns over the event window from -8 to +5 months. Aw and Chatterjee (2004) confirmed similar findings in their articles based on the average return model and MM. They found that acquiring companies experienced a negative performance ranging from -1.2% to -8.07% in cross-border merger and acquisition activities.…”
Section: Short-term Performance Of Cross-border Manda Activities Of Acqsupporting
confidence: 87%
“…Danbolt (1995) made a comparison study for acquiring firms from various countries and concluded that UK acquiring firms earn significant negative abnormal returns over the event window from -8 to +5 months. Aw and Chatterjee (2004) confirmed similar findings in their articles based on the average return model and MM. They found that acquiring companies experienced a negative performance ranging from -1.2% to -8.07% in cross-border merger and acquisition activities.…”
Section: Short-term Performance Of Cross-border Manda Activities Of Acqsupporting
confidence: 87%
“…Despite this, much of the empirical work on the UK focuses on outward acquisitions (Aw & Chatterjee 2000: Gregory & McCorriston 2005: Conn et al,. 2005) with only Danbolt (1995), (2004) and Danbolt & Maciver (2012) focusing on inward acquisitions into the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The value creation potential of cross-border transaction for shareholders of the bidder remains unclear. Studies report positive value effects of cross-border acquisitions (Gleason et al 2002;Chari et al 2010 for emerging market targets) neutral effects (Gregory and McCorriston 2005), and negative effects (Aw and Chatterjee 2004;Ferreira et al 2010). Carapeto et al (2010) analyze acquisitions of distressed targets.…”
Section: Literature and Predictions 21 Related Literaturementioning
confidence: 99%
“…During weak markets acquirers are more likely to have undervalued stock and would potentially over-pay for assets when using shares instead of cash. H2: Share transactions perform stronger in boom markets while cash transactions are favorable in weak markets Recent studies document that conglomerate and cross-border transactions may create less value for shareholders of bidders (Devos et al 2009;Hoberg and Philiips 2010;Aw and Chatterjee 2004). A frequently provided explanation is the increased complexity of transactions in new industries and markets caused by more difficult integration processes.…”
Section: Specific Predictionsmentioning
confidence: 99%